Mobility as a Service in Nowadays Transportation Schemes: An Approach to Go-Jek`s Operational Challenges on its Indonesian Operation. - Carolina Escobar; Juan Fernando Quintero Franco; Yoga Pandalungan (AIBPM Publisher, 2019)
The Case Study aims to get a viable solution on real corporate challenges that Asian companies face in the development of their commercial activities. For this scenario, the company to be taken into consideration will be â€œGo-Jekâ€, an Indonesian company based in Jakarta, which focuses its primary activity in ride-hailing (carpooling) using motorbike taxis, it offers 18 app-based on-demand services; Go-Jek, nevertheless, encounters challenges regarding its regulation and acceptance by independent motorbike companies. Based on the previous statement and due to the lack of laws regulating the business, Go-Jek has an uncertain future of developing its commercial activities to a broader market share. Correspondingly, the case study will be focused on proposing a viable solution for reducing frictions and possible accidents between the company and conventional taxis or any private transportation system already implemented. Keywords: Ride-hailing, Startup, application, motorbikes, Indonesia.